Positive Response to Cardiac Resynchronization Therapy Reduces Arrhythmic Events After Elective Generator Change in Patients with Primary Prevention CRT‐D. (27th August 2014) - SEBAG, FREDERIC A.; LELLOUCHE, NICOLAS; CHEN, ZHONG; TRITAR, AMINE; O'NEILL, MARK D.; GILL, JASWINDER; WRIGHT, MATTHEW; LECLERCQ, CHRISTOPHE; RINALDI, CHRISTOPHER A.
Arrhythmic Outcome After CRT‐D Device Replacement Introduction Cardiac resynchronization therapy (CRT) and implantable cardioverter‐defibrillators (ICD) are effective therapies for heart failure (HF) patients with cardiac dyssynchrony. Patients receiving primary prevention CRT‐defibrillator that positively remodel might no longer qualify for ICD indication due to CRT‐induced left ventricular ejection fraction (LVEF) improvement. We aimed to evaluate the outcome of CRT‐D patients at the time of device replacement (DR). Methods and Results Patients undergoing primary prevention CRT‐D DR were prospectively included from November 2007 to March 2011 in 2 centers. CRT response was as defined as ≥1 NYHA class improvement and an increase in LVEF ≥10%. Before DR, all patients underwent echocardiography and device interrogation. Patients without theoretical ongoing ICD indication (TOII) at DR were defined as those with LVEF ≥40% without appropriate ICD therapy (appropriate therapy) during the first ICD service‐life. A total of 107 consecutive patients were enrolled. Sixty‐one patients (57%) were considered CRT responders after the index procedure. At the time of DR (56.4 ± 14.4 months from initial implant), 87% of CRT responders were free of appropriate therapy, compared with 70% of CRT nonresponders (P = 0.02). Thirty‐nine patients (37%) did not meet the criteria for TOII. During follow‐up (mean 26.4 ± 14.4 months after DR), 37 patients (95%) without TOII were free of appropriate therapy versus 49 of 68 patients (72%) with ongoing TOII (P = 0.007). By multivariable analysis, the only independent predictor of appropriate therapy after DR was TOII (hazard ratio = 6.43; P = 0.01). Conclusion Absence of theoretical ICD indication occurs in more than one‐third of CRT‐D patients undergoing DR. In addition, appropriate therapy rate is relatively low (2.2% per year) in this subgroup of patients.